A new insight into dental implant treatment for trauma-induced edentulism and associated temporomandibular joint disorders: A Case Report - Novianti, Vita Mulya Passa; Pramudita, Seto; Bonifacius, Setiawan; Rikmasari, Rasmi (Universitas Padjadjaran, 2024)
ABSTRACT Introduction: Anterior implant placement is always challenging, especially when it is caused by trauma. Treatment preference is not only because of bone sufficiency but also aesthetic considerations. The complications aggravated by trauma and temporomandibular joint disorder need particular emphasis. The aim of this case report is to describe a new insight into dental implant treatment for trauma-induced edentulism and associated temporomandibular joint disorders. Case report: A 24-year-old woman had a motor vehicle accident. Her four anterior mandibular teeth were extracted through fractures. The patient also complained of clicking in both jaws during mouth opening. A bone graft and modification provisoris-stabilization splint were applied before definitive treatment. Furthermore, a 4-unit Porcelain Fused to Metal (PFM) implant-supported-fixed partial denture was done to replace the missing teeth. Conclusion: New insight into dental implant treatment for trauma-induced edentulism and associated temporomandibular joint disorders with replacement of several anterior mandibular missing teeth due to trauma with temporomandibular disorders could be treated with dental implant modification splint that functions as a temporary restoration as well, which was an alternative treatment option. The patient was satisfied with the result of the treatment, especially in the aesthetic aspect.KEYWORDSdental implant, trauma, temporomandibular joint disorders, splint